Properties of model reduction techniques based on the retention of first- and second-order information - Krajewski, Wiesław; Lepschy, Antonio; Viaro, Umberto (Zielona Góra: Uniwersytet Zielonogórski)
In the recent literature on model simplification considerable interest has been focused on the techniques leading to reduced models that match a suitable number of both first-order and second-order information indices.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka